Gambaran Pengetahuan Ibu tentang KB Suntik 1 Bulan di Klinik Pratama Tanjung Deli Tua Tahun 2021 - Bernadetta Ambarita; Agnes Dwi Sari Hura (JINTAN: Jurnal Ilmu Keperawatan, 2021)
Introduction : Contraceptive injections are one of the contraceptive methods available in Indonesia that serve to prevent the occurrence of pregnancy through hormonal injections. Hormonal contraceptive type birth control injections one of them injectable kb 1 month. This 1-month injectable birth control can prevent egg release or ovulation every month. In addition, this kb also thickens cervical mucus, making it difficult for sperm to move through the cervix. This contraceptive also thins the lining of the uterus so that the fertilized egg is more difficult to implant in the uterus. Method : This study aims to find out an overview of the mother's knowledge about 1 month injectable birth control at Klinik Pratama Tanjung Deli Tua in 2021. This research uses descriptive methods. The samples in this study are all kb acceptors who are still active and visited Klinik Pratama Tanjung Deli Tua in 2021 with a total of 30 respondents. Researchers used primary and secondary data that was processed using SPSS and presented using open tables. Result : The results of the study were as follows: of 30 respondents who were knowledgeable with a good category of 8 people (26.7%), followed by enough category knowledge as many as 10 people (33.3%), and knowledge with a category of less than 12 people (40.0%). Conclusion : The lack of knowledge of the mother about the injectable kb 1 month, it is expected that health workers can provide counseling to the new and recurring KB acceptors about the injectable kb 1 month